Tracing the transition of a macro electron shuttle into nonlinear response - Kim, Chulki; Prada, Marta; Qin, Hua; Kim, Hyun-Seok; Blick, Robert H. (AMER INST PHYSICS, 2015)
We present a study on a macroscopic electron shuttle in the transition from linear to nonlinear response. The shuttle consists of a classical mechanical pendulum situated between two capacitor plates. The metallic pendulum enables mechanical transfer of electrons between the plates, hence allowing to directly trace electron shuttling in the time domain. By applying a high voltage to the plates, we drive the system into a controlled nonlinear response, where we observe period doubling. (C) 2015 AIP Publishing LLC.
Keywords: COULOMB-BLOCKADE